Fabrication and Thermal Analysis of Hybrid A356 Aluminium Metal Matrix Composites Prepared by Stir Casting Process - Naik, J. Murali; Jagadeesh, S.K.; Babu, P. Sekhar; Naidu, S.C.V. Ramana Murty; Muruganandhan, P.; Beneston, S. Lionel (Current Materials Science, 2025)
Introduction/ObjectiveElectronic packaging makes use of hybrid A356 aluminium alloy MMCs (matrix metal composites). Enhanced endurance limit, increased production and energy, low maintenance cost, and benefits to the environment, such as reduced noise and airborne pollutants, are among the features that are recommended to be evaluated. This study aimed to analyze the thermal properties of A356 aluminium alloy with graphite (Gr) and boron carbide (B4C) hybrid metal matrix composites. For this purpose, the A356 hybrid composite was primed by the stir casting process with the addition of 5 wt % and 10 wt % of Gr and B4C reinforcements. In general, A356 hybrid composite material thermal analysis is crucial for electrical equipment.MethodsThe liquid-in-filtration method was used to create the hybrid composites, which were then tested thermally for parameters, like melting point, thermal diffusivity, and thermal coefficient of expansion. The thermocouple sensor of a calorimeter was used to examine the disparity in the composites. A thermal analysis tool called TGA was used to visually represent the relationship between a material's weight and temperature.ResultsThe temperature was found to be 300oC at the 0.411 W/g maximum heat flow rate. Thermal conductivity is the ratio of the temperature difference divided by the area of the heat transfer from one substance to another. The thermal coefficient of expansion illustrates how a material's dimensions and weight change as temperature increases.ConclusionThe proportion of the weight of the hybrid composites was found to fall with a rise in the temperature. The melting point curve of the composites demonstrated a little increase in temperature to be accompanied by a sharp increase in heat flow.
Keywords: melting point